ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN UANG DI INDONESIA TAHUN 1999 : Q1 - 2010 : Q4 DENGAN PENDEKATAN ERROR CORECTION MODELS (ECM) - Inung Oni Setiadi (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2013)
Money has a very important role in the modern economy. Money demand function is often used by central banks in various state as a tool to determine the target growth of money or the money supply. Make up money supply to encourage excessive price increases that exceed the level expected in the long run can undermine economic growth. Conversely, if the increase in the money supply to low the debility economic will happen. This study aims to analyze the factors that influence the demand for money in Indonesia in the short and long run. This research used data coherent time or time series period of 1999:Q1 to 2010 : Q4. The data used are quarterly. Model used the tool of error correction model of econometrical analysis. This model can explain the behavior of short and long run. The results showed (1) the inflation variable in the short and long run has positive and significant impact on the demand for money in Indonesia. (2) the interest rate variable in the short run has no significant negative impact and long run has negative and significant impact on the demand for money in Indonesia. (3) the GDP variable in short run is not significant and long run has positive and significant impact on the demand for money in Indonesia. (4) Error Corection Term marked positive and significant indicate valid models and can used to estimate the demand for money in Indonesia. Based on the results of this study concluded that significant inflation variable in influencing the demand for money in Indonesia, both in the short and long run. The interest rate and GDP variable in short run is not significant, while in long run both are significant impact on demand for money in Indonesia. Bank Indonesia as the monetary authority in Indonesia expect maintain monetary stability through a guard against inflation, as the research results in both the short and long run inflation significant influence the demand for money in Indonesia.